Paenibacillus phocaensis sp. nov., isolated from the gut microbiota of a healthy infant. (March 2017) - Tidjani Alou, M.; Rathored, J.; Nguyen, T.T.; Andrieu, C.; Couderc, C.; Brah, S.; Diallo, B.A.; Fournier, P.-E.; Raoult, D.; Dubourg, G.
Abstract: Paenibacillus phocaensis sp. nov. strain mt24 T (= CSUR P2238 = DSM 101777) is a Gram-negative, facultative anaerobic, spore-forming and motile bacilli. This strain was isolated from the stool sample of a healthy infant from Niger. Its genome was estimated to a size of 5 521 415 bp with a 53.54% GC content. It contains 4835 protein-coding genes and 89 RNAs, among which two were 16S rRNA genes. There were also 101 genes (2.09%) identified as ORFans.